CFD-DEM Study of Pleated Filter Plugging Process Based on Porous Media Model - Yinhang Zhang; Xiuhua Men; Shuai Wang; Xiuli Fu; Liwen Chen (Machines, 2022)
The pneumatic conveying process of fine particles through filters was studied by CFD-DEM simulation method. The porous media model and porous structure were used to simulate the airflow state and the blocking effect of fine particles when they flowed through the filter. Under different particle feed rates and initial particle velocities, the effects of the plugging rate and settling velocity in pleated filters were analyzed, and the effect of particle deposition height on fluid zone was studied. The results showed that particles should avoid the feed rate of 250–750 g/s and choose the initial particle velocity of 3–6 m/s to achieve lower plugging rate and faster settling velocity. The position of the filter should avoid the particle inlet to avoid the increase of non-uniformity. Timely cleaning of particles in the filter box can improve the filtering performance.